Monetary and macroprudential policy complementarities: Evidence from European credit registers - Carlo Altavilla; Luc Laeven; José-Luis Peydró (European Central Bank (ECB), 2020)
We document that there are strong complementarities between monetary policy and macroprudential policy in shaping the evolution of bank credit. We use a unique loanlevel dataset comprising multiple credit registers from several European countries and different types of loans, including corporate loans, mortgages and consumer credit. We merge this rich information with borrower and bank-level characteristics and with indicators summarising macroprudential and monetary policy actions. We find that monetary policy easing increases both bank lending and lending to riskier borrowers, especially when there is a more accommodative macroprudential environment. These effects are stronger for less capitalised banks. Results apply to both household and firm lending, but they are stronger for consumer and corporate loans than for mortgages. Finally, for firms, the overall increase in bank lending induced by an accommodative policy mix is stronger for more (ex ante) productive firms than firms with high ex ante credit risk, except for banks with low capital.
Keywords: E51; E52; E58; G21; G28; 330; monetary policy; macroprudential policy; corporate and household credit; euro area